The Kallikrein Inhibitor from Bauhinia bauhinioides (BbKI) shows antithrombotic properties in venous and arterial thrombosis models - Brito, Marlon V.; Oliveira, Cleide de; Salu, Bruno R.; Andrade, Sonia A.; Malloy, Paula M. D.; Sato, Ana C.; Vicente, Cristina P.; Sampaio, Misako U.; Maffei, Francisco Humberto de Abreu [UNESP]; Oliva, Maria Luiza V. (Elsevier B.V., 2014)
The Bauhinia bauhinioides Kallikrein Inhibitor (BbKI) is a Kunitz-type serine peptidase inhibitor of plant origin that has been shown to impair the viability of some tumor cells and to feature a potent inhibitory activity against human and rat plasma kallikrein (Kiapp 2.4 nmol/L and 5.2 nmol/L, respectively). This inhibitory activity is possibly responsible for an effect on hemostasis by prolonging activated partial thromboplastin time (aPTT). Because the association between cancer and thrombosis is well established, we evaluated the possible antithrombotic activity of this protein in venous and arterial thrombosis models. Vein thrombosis was studied in the vena cava ligature model in Wistar rats, and arterial thrombosis in the photochemical induced endothelium lesion model in the carotid artery of C57 black 6 mice. BbKI at a concentration of 2.0 mg/kg reduced the venous thrombus weight by 65% in treated rats in comparison to rats in the control group. The inhibitor prolonged the time for total artery occlusion in the carotid artery model mice indicating that this potent plasma kallikrein inhibitor prevented thrombosis. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Blood coagulation; Kallikrein; Kunitz inhibitor; Thrombosis; Trypsin inhibitor; Tumor cells